Simulação do impacto do consumo de água no custo operacional de um modelo computacional de sistema de abastecimento de água - CORRÊA, Camila da Costa (2019)
The water supply system is essential for good management of water resources, as it assists in the monitoring of them. In the case of natural resources management, it is necessary to have precise factors influencing its management. The following study aimed at the simulation of the electric energy consumption through the modeling of pumping systems with varied scenarios using the EPANET 2.0. Program that allows hydraulic, dynamic and static simulations with a variety of existing parameters. Based on the results obtained, it was possible to observe the difference in the cost of electric energy in different scenarios and flows, being the power of the motorcycle pump a factor of essential importance, where the simulations are made with commercial powers that are usually used in the market to attend to pressure range and speed governed in standard and with minimum non-commercial powers that also meet the same. In addition to the possibility of using the minimum power that meets the consumption demand, the work has as main scope, the analysis of the presence or not of the application of tariffs in relation to the consumption per capita, considering that its absence increases the consumption of water and consequently the electric power consumption. Reducing the consumption of electric energy in pumping systems allows the significant reduction in the expenses related to them.